Prognostic values of baseline, interim and end-of therapy 18F-FDG PET/CT in patients with follicular lymphoma - Zhou Y; Zhao Z; Li J; Zhang B; Sang S; Wu Y; Deng S (Cancer Management and Research, 2019)
Yeye Zhou,* Zixuan Zhao,* Jihui Li, Bin Zhang, Shibiao Sang, Yiwei Wu,* Shengming DengDepartment of Nuclear Medicine, The First Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China*These authors contributed equally to this workPurpose: In the present study, we aimed to investigate the role of baseline, interim and end-of treatment positron emission tomography/computed tomography (PET/CT) in assessing the prognosis of follicular lymphoma (FL).Methods: A total of 84 FL patients were retrospectively analyzed in this study. Baseline (n=59), interim (n=24, after 2–4 cycles) and end-of treatment (n=43) PET/CT images were re-evaluated, and baseline maximum standardized uptake value (SUVmax), total metabolic tumor volume (tMTV) and total lesion glycolysis (TLG) were recorded. Interim (I-PET) and end-of treatment (E-PET) PET/CT responses were interpreted by Deauville five-point scale (D-5PS) and International Harmonization Project criteria (IHP). Survival curves were calculated by Kaplan-Meier curves, and differences between groups were compared by log-rank test.Results: The 2-year progression-free survival (PFS) of the high- and low-TLG groups was 57.14% and 95.56%, respectively (p=0.0001). The 2-year overall survival (OS) of the high- and low-TLG groups was 62.50% and 100%, respectively (p<0.0001). Multivariate analysis showed that TLG was an independent prognostic factor for PFS (p=0.001, HR=6.577, 95% CI=2.167–19.960) and OS (p=0.030, HR=19.291, 95% CI =2.689–137.947). Besides, Eastern Cooperative Oncology Group (ECOG) was the independent prognostic factor for OS (HR=8.924, 95% CI=1.273–62.559, p=0.028). Interim PET results based on D-5PS or IHP criteria were not significantly correlated with PFS (all p>0.05). However, E-PET results using D-5PS and IHP criteria were statistically significant (p=0.0001 and p=0.006). The D-5PS showed stronger prognostic value compared with IHP criteria. The optimal cutoff value of ΔSUVmax% was 66.95% according to I-PET and 68.97% according to E-PET. However, only the ΔSUVmax% from the baseline to the end-of therapy yielded statistically significant results in the prediction of PFS (p=0.0002).Conclusion: Our findings indicated that the baseline TLG and E-PET results were significantly associated with prognosis in patients with FL.Keywords: follicular lymphoma, PET/CT, MTV, TLG, D-5PS, IHP